Isoflurane has no effect on cognitive or behavioral performance in a mouse model of early-stage Alzheimer’s disease - Borgstedt, Laura; Bratke, Sebastian; Blobner, Manfred; Pötzl, Christoph; Ulm, Bernhard; Jungwirth, Bettina; Schmid, Sebastian (Frontiers in Neuroscience, 2022)
Background: Patients with Alzheimer’s disease show a sex-dependent decline of cognitive and behavioral performance. It is controversially discussed whether general anesthesia itself can aggravate or even cause this neurocognitive decline. Therefore, we investigated the effect of general anesthesia on neurocognitive and behavioral function and amyloidopathy in a mouse model of early-stage Alzheimer’s disease with respect to sex. Methods: After governmental approval 10 months old Tg2576 mice and wild type (total 85 mice) either underwent general anesthesia with 1.0 minimal alveolar concentration of isoflurane for 2 hours or were not exposed to isoflurane (controls). Following cognitive and behavioral testing using the modified hole board test, brains were investigated regarding amyloidopathy, inflammation, and apoptosis. Data were analyzed using repeated measure analysis of variance and univariate analysis of variance. Results: Tg2576 mice showed a decline in memory function (p<0.001), less anxiety (p=0.022 and p=0.024), increased locomotor activity (p=0.025), and impaired fine motor skills (p<0.001). Amyloid precursor protein (p<0.001), soluble amyloid-beta (p<0.001) and insoluble amyloid deposits (p<0.001) were increased in Tg2576 animals. Neither sex nor exposure to isoflurane had an effect on cognitive or behavioral testing or expression of amyloid-related biomarkers. Discussion and conclusion: We found that 10 months old Tg2576 showed typical signs of early-stage Alzheimer’s disease and corresponding histopathological alterations. Relevant sex-specific differences or an effect of isoflurane anesthesia could not be detected at this early stage of the disease.